Soil Bunding Capacity of Some Grasses at Deochanda Experiment Station, D.V.C. - Pandey, S.N.; Chakravarty, R.K.; Teotia, S.P. Singh (Journal of Soil and Water Conservation, 2022)
Since long the grasses have been recognised as soil stabilisers and play a vital role in soil and water conservation. The grasses have been found to be very effcctive in controlling soil erosion and have wide adoptability for different soil and climatic conditions. Studies conducted in different parts of the world have indicated that erosion can be effectively controlled by adopting suitable cover craps. The grass roots have been observed to bind the soil practicics with their net work of roots and reduce the erosive action to a great extent.